Oil & Community Welfare: A Case Study on People Oil Mining in Indonesia - Brata, Nugroho Trisnu (Universitas Negeri Semarang, 2014)
Usually in the oil mining area was exploited by oil company that under licensed from the state. Nevertheless on an oil mining field in East Java Province in Indonesia there is people oil mining that exploited and distributed by the people. They are working on the people oil mining area. Working is a phenomenon inherent to adults in satisfying their needs. People work for a multitude of motivation. Working may lead a particular worker to occupy certain social status within the society. This paper aims to examine the phenomenon of people working in the oil distribution link from people oil miningÂ to consumer. More specifically, this study aims to describe the impacts of working in the oil mining on the minersâ social and economic life. The method used in this research is ethnography. Data were collected through observation, in-depth interviews, note taking, and recording. The location of research is in a petroleum artisanal mining area in East Java Province. The results showed that the impact of working in the oil distribution link from people oil mining to consumer is the generation of income used to meet the basic needs, to purchase personal means of transportation, to purchase some piece of land, and to pay for the childrenâs education.Biasanya ladang minyak dieksploitasi perusahaan yang memperolehy ijin dari negara. Akan tetapi ada ladang minyak di Jawa Timur yang dieksploitasi oleh masyarakat. Mereka bekerja pada ladang sepertiÂ itu. Pekerja memiliki motivasi bermacam-macam dalam pekerjaanya. Bekerja membantu seseorang memperoleh status tertentu dalam masyarakat. Artikel ini bertujuan untuk menelaah fenomena pekerja ladang minyak. Pertanyaan yang ingin dijawab dalam penelitian ini adalah: (1) mengapa orang bekerja di ladang minyak?; (2) bagaimana kesejahteraan mereka?; dan (3) bagaimana pengaruh bekerja di ladang minyak pada kehidupan sosial dan ekonomi para pekerja?. Penelitian menggunakan metode etnografi. Penelitian dilakukan di Jawa Timur. Hasil penelitian menunjukkan bahwa pendapatan yang diperoleh digunakan untuk memenuhi kebutuhan dasar, membeli alat transportasi pribadi, membeli tanah dan membayar pendidikan anak.